2021
DOI: 10.3389/fphys.2021.728208
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circular RNA Expression Profiles in White Adipocytes and Their Roles in Adipogenesis

Abstract: Obesity and its related metabolic diseases have become great public health threats worldwide. Although accumulated evidence suggests that circRNA is a new type of non-coding RNAs regulating various physiological and pathological processes, little attention has been paid to the expression profiles and functions of circRNAs in white adipose tissue. In this study, 3,771 circRNAs were detected in three stages of white adipogenesis (preadipocyte, differentiating preadipocyte, and mature adipocyte) by RNA-seq. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…A RNA-Seq study has identified 3771 circRNAs in the three stages of white fat formation. Statistical analysis showed that nearly 10% of the genes expressing linear RNA in adipocytes could generate circRNAs, and 40% of the cells produced multiple circRNA isoforms . In this study, 8165 circRNAs overlapped in 3282 genes.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…A RNA-Seq study has identified 3771 circRNAs in the three stages of white fat formation. Statistical analysis showed that nearly 10% of the genes expressing linear RNA in adipocytes could generate circRNAs, and 40% of the cells produced multiple circRNA isoforms . In this study, 8165 circRNAs overlapped in 3282 genes.…”
Section: Discussionmentioning
confidence: 94%
“…Statistical analysis showed that nearly 10% of the genes expressing linear RNA in adipocytes could generate circRNAs, and 40% of the cells produced multiple circRNA isoforms. 37 In this study, 8165 circRNAs overlapped in 3282 genes. Among the circRNA host genes, 46.44% could produce a single circRNA, and the rest could produce two or more circRNAs.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study identified circRNAs profiles in white and brown AT, which provided circRNA candidates for regulating adipose formation. 186,187 Studies suggested that circ-SAMD4A increased preadipocyte differentiation, 188 and circArhgap5-2 played an essential role in adipogenesis and lipid metabolism. 189 Evidence suggests that downregulated hsa_circ_000839 in patients with BC exhibits a negative correlation with BMI, but the underlying mechanism is still unclear.…”
Section: Circrnas In Obesity-associated Diseasesmentioning
confidence: 99%